Design of a Desktop-Based PDD Management Information and Archiving System at PT PUSRI - Dian Pertiwi; Depi Linda (oneamrd (One a Mllions Dreams Corporation), 2025)
This study aims to develop and implement a desktop-based archival management information system for the PPD division of PT Pupuk Sriwidjaja Palembang (Pusri) in Lampung, addressing the company's ongoing issues with physical document deterioration, loss, and retrieval inefficiencies. Key findings demonstrate that transitioning from paper to electronic documents (e-documents) is a highly strategic preventive measure; it safeguards physical archives against threats such as decay, humidity, fire, and natural disasters, while simultaneously boosting operational efficiency through easy backup duplication. The implementation of a MySQL relational database effectively eliminates time-consuming manual searches; the structured database—utilizing indexes and metadata—enables data retrieval within seconds, thereby drastically increasing employee productivity. Furthermore, the inclusion of role-based access authentication proves effective in restricting access to sensitive documents, protecting internal data confidentiality against misuse and information leaks. Methodologically, the study employs the Structured Systems Analysis and Design (SSAD) approach, providing a structured framework for mapping business processes. Through the use of Context Diagrams, Data Flow Diagrams (DFD), Entity-Relationship Diagrams (ERD), and program flowcharts, non-technical requirements were accurately translated into Java code, minimizing logic errors during software development. Consequently, the developed system successfully assists the company in digitally organizing documents, streamlining file retrieval, and significantly reducing the risk of physical archive loss or damage, resulting in a holistic, secure, and highly reliable archival management ecosystem